2019
DOI: 10.3389/fonc.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

Review of PD-1/PD-L1 Inhibitors in Metastatic dMMR/MSI-H Colorectal Cancer

Abstract: There are a wide range of therapies for metastatic colorectal cancer (CRC) available, but outcomes remain suboptimal. Learning the role of the immune system in cancer development and progression led to advances in the treatment over the last decade. While the field is rapidly evolving, PD-1, and PD-L1 inhibitors have a leading role amongst immunomodulatory agents. They act against pathways involved in adaptive immune suppression resulting in immune checkpoint blockade. Immunotherapy has been slow to impact the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 39 publications
2
124
0
1
Order By: Relevance
“…The very poor prognosis for patients with MSI-H tumors is likely a combination of a more aggressive tumor and a poorer response to therapy. The very poor response to first-line treatment in patients with MSI-H tumors reported here, underlines the importance of evaluating immunotherapy upfront [26].…”
Section: Discussionmentioning
confidence: 69%
“…The very poor prognosis for patients with MSI-H tumors is likely a combination of a more aggressive tumor and a poorer response to therapy. The very poor response to first-line treatment in patients with MSI-H tumors reported here, underlines the importance of evaluating immunotherapy upfront [26].…”
Section: Discussionmentioning
confidence: 69%
“…A high TMB, as well as MSI-H as a predictive biomarker for response in mCRC, was revealed by previous studies, and patients carrying these characteristics are thought to be susceptible to immune checkpoint blockade (ICB) (20). The KEYNOTE-164 study evaluating pembrolizumab in MSI-H mCRC previously treated with more than one line of therapy showed that overall survival (OS) rates were 76% with a 41% PFS rate at 12 months (21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an MSI-stable or -low (MSS or MSI-L) phenotype (instability in <30% of microsatellites) indicates proficient MMR (pMMR) [1]. Lynch syndrome, an inherited syndrome caused by autosomal dominantly inherited germline mutations in one of the MMR genes (hMLH1, hMSH2, hMSH6, hPMS2, EPCAM), is seen in 3% of all CRC patients, whereas sporadic MSI-H status, most commonly due to inactivation of hMLH1, is seen in about 5-20% of all CRCs [2][3][4][5][6].…”
Section: Msi/mmr Statusmentioning
confidence: 99%